Analysis of dribbling-distance coverage performed by futsal athletes Indonesian Futsal League 2021 - Doewes, R. I.; Elumalai, G.; Azmi, S. H. (Revista Brasileira de Medicina do Esporte, 2022)
Introduction: Futsal players must master dribbling in attack and defense positions for a more significant competitive advantage. Optimizing technical control can positively influence decision-making. However, the literature lacks comparative analyses focused on the coverage distance of this technique in sports finals and semifinals.